PENGARUH KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS PELAYANAN PADA DINAS PERTANIAN DAN KETAHANAN PANGAN KABUPATEN WAJO - Amrizal Akmul; Yudi Rafial Hadi; Hasfikah Hasfikah (Jurnal Ilmu Administrasi Negara, 2023)
The background of this research is because the quality of services provided to the Agriculture and Food Security Service of Wajo Regency is not yet optimal, as there are still some employees who lack technical skills in carrying out their duties. The purpose of this study was to determine the effect of Human Resource Competence on Service Quality at the Agriculture and Food Security Office of Wajo Regency. The population in this study were the people who received services from the Wajo District Agriculture and Food Security Service for the last 2 months, totaling 28 people, all of whom were used as respondents using the saturated sample technique. Data collection was carried out using a questionnaire and documentation study. While the data analysis technique used is a quantitative descriptive analysis technique and associative analysis technique. The results of the study show that: Human Resource Competence has a strong influence on Service Quality at the Agriculture and Food Security Office of Wajo Regency. It is suggested to the leadership of the Agriculture and Food Security Service of Wajo Regency, that they can strive to improve the quality of their service to the community, namely through increasing the competence of human resources, in this case the employees who work in it together with other factors that affect the quality of service in their organization.